Pengaruh Bakat dan Dukungan Keluarga terhadap Motivasi Belajar Mahasiswa Penerima KIP-K Universitas Pendidikan Ganesha - I Gede Agus Setiawan; I Putu Arya Dharmayasa (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to determine (1) the influence of talent on the learning motivation of KIP-K recipient students at Universitas Pendidikan Ganesha, (2) the influence of family support on the learning motivation of KIP-K recipient students at Universitas Pendidikan Ganesha, and (3) the simultaneous influence of talent and family support on the learning motivation of KIP-K recipient students at Universitas Pendidikan Ganesha. The research sample consisted of 355 students selected using stratified random sampling. Data collection was conducted through the distribution of questionnaires. The data were analyzed using multiple linear regression analysis assisted by statistical data processing software. The results showed that: (1) Talent partially has a positive and significant influence on the learning motivation of KIP-K recipient students, as indicated by a t-value of 18.944 and a significance value of 0.000; (2) Family support partially has a positive and significant influence on the learning motivation of KIP-K recipient students, as indicated by a t-value of 17.591 and a significance value of 0.000; (3) Simultaneously, the variables of talent and family support have a significant influence on students' learning motivation with a significance value of 0.000. The coefficient of determination (R2) value of 0.756 indicates that the combined contribution of talent and family support variables is 75.6% toward the variation in learning motivation among KIP-K recipient students at Universitas Pendidikan Ganesha.